Strengthening Maqāṣid al-Sharī’ah Values in Halal Traceability: Evidence and Analysis of Block Chain Based on Halal Supply Chain Applications - Nashirudin, Muh.; Ramadhan; Almira Keumala Ulfah (Al-Manahij: Jurnal Kajian Hukum Islam, 2024)
Halal traceability is one of the government's focus in developing the halal industry. By adopting a blockchain system, halal traceability is undoubtedly transparent. However, this transparency also needs to be analyzed using maqāṣid al-sharī'ah. This analysis is used to analyze the extent of the application of maqāṣid al-sharī'ah values in halal traceability. The results of the study state that the application of halal traceability has fulfilled the elements of maqāṣid al-sharī'ah, such as transparency, accountability, responsibility, and justice. Therefore, the blockchain-based halal traceability application model is appropriate and relevant to Islamic values.